Synthesis, characterization and photocatalytic properties of nanostructured CoFe2O4 recycled from spent Li-ion batteries. (September 2017) - Moura, M.N.; Barrada, R.V.; Almeida, J.R.; Moreira, T.F.M.; Schettino, M.A.; Freitas, J.C.C.; Ferreira, S.A.D.; Lelis, M.F.F.; Freitas, M.B.J.G.
Abstract: In this study, cobalt (Co) was recycled from spent lithium ion batteries (LIBs) and used to synthesize cobalt ferrite (CoFe2 O4 -LIBs), which was applied as a catalyst for heterogeneous photo Fenton reactions that discolored methylene blue (MB) dye. The co-precipitation method was used to synthesize CoFe2 O4 -LIBs and CoFe2 O4 -R nanoparticles with spinel structures using as raw materials of the LIB cathodes and commercial reagents. X-ray diffraction (XRD) identified the formation of spinel-type CoFe2 O4, which formed clusters that could be seen under scanning electron microscopy (SEM) analysis and nanometric particles seen under transmission electron microscopy (TEM). Inductively Coupled Plasma Optical Emission Spectrometer (ICP OES) analysis was used to determine the concentrations of metals present in the ferrite, which reached 6.5% (w/w) of Co. The optimal conditions for discoloring the dye were evaluated using a factorial design. Using CoFe2 O4 as a catalyst, the best conditions for catalytic reaction were pH 3, 30.0 mg of catalyst, and 8.0 mL of H2 O2 73% (v/v). Discoloration efficiencies of 87.3% and 87.7% were obtained from CoFe2 O4 -R and CoFe2 O4 -LIBs, respectively. Therefore, CoFe2 O4 -LIBs proved to be an efficient catalyst for discoloring MB dye using heterogeneous photo-Fenton reactions. This work is of scientific, social, economic, and environmental interest. It investigates the process of synthesizing, characterizing CoFe2 O4 LIBs and the efficiency of degrading MB dye, subjects that have economic and environmental, and therefore, social interest. The work has scientific interest particularly because of the correlation between the structure of the recycled material and its catalytic properties. Graphical abstract: Nanoparticles of CoFe2 O4 synthesized using the cathodes of LIBs as raw materials. Highlights: Cobalt was recycled from spent lithium ion batteries to synthesize CoFe2 O4 . Nanoparticles of CoFe2 O4 with type spinel structures was synthesized. CoFe2 O4 was applied as a catalyst in heterogeneous photo Fenton reactions. CoFe2 O4 was characterized by XRD, SEM, TEM, and ICP OES techniques.